Type I and III Interferon in the Gut: Tight Balance between Host Protection and Immunopathology - Pott, Johanna; Stockinger, Silvia (Frontiers in Immunology, 2017)
The intestinal mucosa forms an active interface to the outside word, facilitating nutrient and water uptake and at the same time acts as a barrier towards the highly colonized intestinal lumen. A tight balance of the mucosal immune system is essential to tolerate harmless antigens derived from food or commensals and to effectively defend against potentially dangerous pathogens. Interferons (IFN) provide a first line of host defence when cells detect an invading organism. Whereas type I IFN were discovered almost 60 years ago, type III IFN were only identified in the early 2000s. It was initially thought that type I IFN and type III IFN performed largely redundant functions. However it is becoming increasingly clear that type III IFN exert distinct and non-redundant functions compared to type I IFN, especially in mucosal tissues. Here we review recent progress made in unravelling the role of type I/III IFN in intestinal mucosal tissue in the steady state, in response to mucosal pathogens and during inflammation.